1975
DOI: 10.1063/1.861083
|View full text |Cite
|
Sign up to set email alerts
|

Variable viscosity effects on the onset of convection in porous media

Abstract: The onset of convection in a horizontal, isotropic, water-saturated porous medium is considered. The temperature difference between the top and bottom is as large as 250 °C. The effects of an eightfold variation in kinematic viscosity are included. The critical Rayleigh number is found to be substantially reduced from the classical value although the associated wavenumber is nearly the same. Neutral mode streamline and isotherm patterns are considerably distorted in the vertical direction in distinction to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 4 publications
0
38
0
Order By: Relevance
“…Then R 24 to 240 if the bulk permeability of the convecting medium is 4 to 40 millidarcys. Because of the large thermal-expansion coefficient (Straus and Schubert, 1977) and the temperature-dependent viscosity of water (Kassoy and Zebib, 1975), R c for the ocean crust is less than 10, whether the top of the cell is permeable or impermeable (Ribando et al, 1976). Therefore, convection in the basement is indicated strongly.…”
Section: Discussionmentioning
confidence: 99%
“…Then R 24 to 240 if the bulk permeability of the convecting medium is 4 to 40 millidarcys. Because of the large thermal-expansion coefficient (Straus and Schubert, 1977) and the temperature-dependent viscosity of water (Kassoy and Zebib, 1975), R c for the ocean crust is less than 10, whether the top of the cell is permeable or impermeable (Ribando et al, 1976). Therefore, convection in the basement is indicated strongly.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in a notable study, commenting on [25][26][27], Nield [30,31] argued that the effect of property variation on free convection is artificial and should disappear if one uses an effective Rayleigh number based on mean values. Nield [31] showed that, if the mean values are used, the critical Rayleigh number remains unaltered, which indicates that the flow of a fluid with temperature-dependent viscosity is no less stable than a constant-property one.…”
Section: Nusselt Number Bénard Problemmentioning
confidence: 99%
“…fluid flow patterns compared to constant property solutions [24]. Some authors (see for example [25][26][27][28]) have investigated natural convection with temperature dependent viscosity while keeping the other fluid properties constant (this assumption is known to be valid for some fluids [29]). …”
Section: Nusselt Number Bénard Problemmentioning
confidence: 99%
“…The fundamental analysis of convection through porous media with temperature dependent viscosity is driven by several contemporary engineering applications from the cooling of electronic devices to porous journal bearings and is important for studying the variations in constitutive properties. The effect of variable viscosity for convective heat transfer through porous media has also been widely studied (e.g., [13][14][15][16][17][18][19]). The effect of variations in viscosity on the instability of flow and temperature fields are discussed by Kassoy and Zebib [13] and Gray et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of variable viscosity for convective heat transfer through porous media has also been widely studied (e.g., [13][14][15][16][17][18][19]). The effect of variations in viscosity on the instability of flow and temperature fields are discussed by Kassoy and Zebib [13] and Gray et al [14]. Lai and Kulacki [15] considered the variable viscosity effect for mixed convection along a vertical plate embedded in a saturated porous medium.…”
Section: Introductionmentioning
confidence: 99%